Parametric Sensitivity of Hemispheric Albedo Symmetry Weakly Constrains Shortwave Cloud Radiative Feedbacks in the Community Atmosphere Model Version 6 - Aiden Jönsson; Maria Rugenstein; Frida A.‐M. Bender; Daniel McCoy; Trude Eidhammer (Geophysical Research Letters)
Abstract Earth's albedo is symmetric between the northern and southern hemispheres (NH and SH, respectively) because SH clouds compensate for higher NH clear‐sky albedo, a feature that climate models have difficulty capturing. We assess how parameterized processes affect a model's cloud albedo and albedo symmetry using a perturbed parameter ensemble (PPE) of atmospheric simulations. Parameters most significant to simulated albedo symmetry impact precipitation, turbulent dissipation, and sea salt aerosol emissions. Constraining the PPE's shortwave cloud feedbacks using the observed albedo symmetry yields a range of +0.61 ± 0.24 W m−2 K−1 (66% confidence), which is stronger than that of the model's control simulation due to parameter settings that lead to greater loss of subtropical low clouds and weaker negative cloud phase feedback. Although these settings would reduce cloud albedo bias compared to the control simulation, we find that albedo symmetry has limited potential as a constraint for cloud feedbacks on its own.